Effects of Orbital Motion on the Boundary Layer Flow on a Spinning Disk - Munekata, Mizue; Jobi, Naoya; Ikebe, Koichi; Yoshikawa, Hiroyuki (Scientific Research, 2012)
The objective of this study is to experimentally examine the effects of orbital motion on the boundary layer flow on a spinning disk. The boundary layer flow on the disk is visualized by the oil flow method, and velocity in the boundary layer is measured by the hot-wire method. For the oil flow pattern in the case of spinning motion only, streaks are clearly observed on the disk as transient vortices, but by adding orbital motion to the spinning motion, we find that streaks are not observed in a certain range of orbital conditions. With increasing orbital motion speed, the laminar region becomes narrower and transition is promoted from the inward region of the disk, regardless of the direction of rotation. Also, with the addition of orbital motion, the velocity profile in the boundary layer becomes more asymmetric with respect to the spin axis of the disk. Furthermore, stationary vortices do not appear on the disk when the orbital speed is beyond a certain critical value. Therefore, the lack of streaks in the oil film pattern when orbital motion is added is due to the spatiotemporal unsteadiness of the flow field on the disk.
Keywords: Velocity Measurement; Flow Visualization; Boundary Layer; Transition; Rotating Disk